Intervensi Kelompok dalam Program Therapeutic Community bagi Warga Binaan Pemasyarakatan Penyalahguna Napza di Lembaga Pemasyarakatan Pemuda Kelas IIA Tangerang - Basrida Ayu Utami; , Sokhivah Sokhivah (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
The stigma given to drug users will make them tend to act in accordance with what is given to them. Positive stigma has a strong meaning, so it tends to have a positive impact on individuals, while negative stigma is given to someone who is considered to deviate from the norm. Stigma towards drug users will become more complex if the handling is not sustainable and can affect the self-concept of drug users. Therapeutic Community is often referred to as the “community method”. Therapeutic Community members interact in structured and unstructured ways to influence attitudes, perceptions, and behaviors related to drug use. Within the Therapeutic Community there is a group approach that provides help to a number of people deliberately grouped based on the problems that person has, where a group is used as a medium to change a behavior.